Cross sectional evaluation of biochemical markers of bone, cartilage, and synovial tissue metabolism in patients with knee osteoarthritis: relations with disease activity and joint damage. Issue 6 (1st June 2001) - Garnero, P; Piperno, M; Gineyts, E; Christgau, S; Delmas, P D; Vignon, E
Abstract : OBJECTIVE: To analyse the relations between the urinary levels of type II collagen C-telopeptide (CTX-II) and glucosyl-galactosyl pyridinoline (Glc-Gal-PYD)—two newly developed biochemical markers of type II collagen and synovial tissue destruction respectively—disease activity and the severity of joint destruction in patients with knee osteoarthritis (OA). The clinical performance of these two new markers was compared with that of a panel of other established biochemical markers of connective tissue metabolism. METHODS: The following biochemical markers were measured in a group of 67 patients with knee OA (mean age 64 years, median disease duration eight years ) and in 67 healthy controls: for bone, serum osteocalcin, serum and urinary C-telopeptide of type I collagen (CTX-I); for cartilage, urinary CTX-II, serum cartilage oligomeric matrix protein (COMP), and serum human cartilage glycoprotein 39 (YKL-40); for synovium, urinary Glc-Gal-PYD, serum type III collagen N-propeptide (PIIINP), serum hyaluronic acid (HA); and for inflammation, serum C reactive protein. Biochemical markers were correlated with pain and physical function (WOMAC index) and with quantitative radiographic evaluation of the joint space using the posteroanterior view of the knees flexed at 30°. RESULTS: All bone turnover markers were decreased in patients with knee OA compared with controls (−36%, −38%, and −52%, p<0.0001 for serum osteocalcin, serum CTX-I and urinary CTX-I, respectively). Serum COMP (+16%, p=0.0004), urinary CTX–II (+25%, p=0.0009), urinary Glc-Gal-PYD (+18%, p=0.028), serum PIIINP (+33%, p<0.0001), and serum HA (+ 233%, p<0.0001) were increased. By univariate analyses, increased urinary Glc-Gal-PYD ( r =0.41, p=0.002) and decreased serum osteocalcin ( r =−0.30, p=0.025) were associated with a higher total WOMAC index. Increased urinary CTX–II ( r =−0.40, p=0.0002) and Glc-Gal-PYD ( r =−0.30, p=0.0046) and serum PIIINP ( r =−0.29, p=0.0034) were the only markers which correlated with joint surface area. By multivariate analyses, urinary Glc-Gal-PYD and CTX-II were the most important predictors of the WOMAC index and joint damage, respectively. CONCLUSION: Knee OA appears to be characterised by a systemic decrease of bone turnover and increased cartilage and synovial tissue turnover. CTX-II, Glc-Gal-PYD, and PIIINP may be useful markers of disease severity in patients with knee OA.